Acceptability of reproductive goals assessment in public mental health care. (12th January 2023) - Goodsmith, Nichole; Dossett, Emily C.; Gitlin, Rebecca; Fenwick, Karissa; Ong, Jessica R.; Hamilton, Alison; Cordasco, Kristina M.
Abstract: Objective: To assess patient and provider perspectives on the acceptability of reproductive goals assessment in public mental health clinics and inform potential tailoring for these settings. Data Sources and Study Setting: Primary qualitative data from patients and providers at four clinics in an urban public mental health system serving individuals with chronic mental illness (collected November 2020–October 2021). Study Design: This was an exploratory qualitative study with patients (English‐speaking women of reproductive age, primarily Black or Latina) and mental health providers (psychiatrists, psychotherapists, case managers, nurses). We examined the acceptability of reproductive goals assessment within mental health care and obtained feedback on two reproductive goals assessment conversation guides: PATH (Pregnancy Attitudes, Timing, and How Important is Pregnancy Prevention) and OKQ (One Key Question). Data Collection: We conducted semi‐structured telephone interviews with 22 patients and 36 providers. We used rapid qualitative analysis to summarize interview transcripts and identified themes using matrix analysis. Principal Findings: Perceptions of reproductive goals assessment were generally positive. Providers said the conversation guides would "open the door" to important discussions, support a better understanding of patients' goals, and facilitate medication counseling and planning. A minority of patients expressed discomfort or ambivalence; several suggested providers ask permission or allow patients to raise the topic. Additional themes included the need for framing to provide context for these personal questions, the need to build rapport before asking them, and the challenge of balancing competing priorities. Many participants found both PATH and OKQ prompts acceptable; some preferred the "conversational" and "open‐ended" PATH phrasing. Conclusions: Participants perceived reproductive goals assessment as a promising practice in mental health care with unique functions in this setting. Areas of discomfort highlight the sensitivity of these topics for some women with chronic mental illness and suggest opportunities to tailor language, framing, and provider training to support effective and appropriate implementation.